The Role of Chatbots in Academic Libraries: An Experience-based Perspective. Issue 3 (3rd July 2022) - Kaushal, Vaishali; Yadav, Rajan
ABSTRACT: Today, with the rapid advancement of technology, Artificial Intelligence (AI)-powered chatbots have become omnipresent across sectors like e-commerce, travel, hospitality, banking, EdTech, etc.; but they still haven't been predominantly adopted by academic libraries. This paper reports on a qualitative study aimed to explore the perceived risks and challenges behind the adoption of chatbots in libraries and how chatbots could help deliver superior experience to all library users as well as stakeholders. We conducted interviews with multiple stakeholders of academic libraries: the library staff, doctoral students and the faculty, to understand their perspectives on the adoption of Chatbots. We used CAQDAS NVIVO 12 content analysis software to analyse the interview transcripts. Our findings suggest that the majority of the stakeholders we interviewed favour the adoption of chatbots, as they believe that integrating chatbot technology with an existing library information system could deliver diverse services, which in turn would help in research and scholarly communication. However, 'perceived risk' with respect to employing chatbots among stakeholders was high. Also, the stakeholders raised some serious concerns with respect to privacy intrusion by chatbots, and with respect to chatbots' comprehension of task complexity, which are issues that must be addressed by chatbot developers while designing them, specifically for libraries.